Light Pieces. - Lunghi, Emilio; Casino Luxembourg - Forum d'Art Contemporain Luxembourg, Luxemburg (Luxemburg : Casino Luxembourg - Forum d'Art Contemporain Luxembourg, 2000)
Flavin, Dan ; Fontana, Lucio ; Kaar, Martin ; Kosuth, Joseph ; Kuball, Mischa ; Kubisch, Christina ; Nauman, Bruce ; Piene, Otto ; Prini, Emilio ; Sonnier, Keith ; et al.
Light Pieces, Casino Luxembourg - Forum d'Art Contemporain Luxembourg, Luxemburg, 05.02-26.03.2000
kunstcatalogus